EFFECTIVENESS OF METACOGNITIVE READING STRATEGY IN NARRATIVE TEXT OF GRADE 9 FOR INDONESIAN EFL SECONDARY LEARNERS - Henny Iswati; Ardhelia Cintara Dwiki Frendy (Wiralodra English Journal, 2022)
During the past decades, the teaching reading has paid a great attention among the scholars in EFL context. Numerous research has been undertaken in particular how the effective of teaching reading. However, relatively few of studies report on the examining metacognitive strategy in teaching reading. To fill this gap, this study is aimed to examine the effectiveness of metacognitive strategy in teaching reading situated in secondary school context. Grounded in quantitative approach with the One-Shot case study design using a Likert-scale questionnaire by Mokhtari and Sheorey (2002). The subjects of this study were 34 students of 9th-grade junior high school at one of the best schools in Surabaya, East Java. The results of this study show that there is 44.12% percent or 15 students have implemented part of this metacognitive reading strategy, namely Global Reading Strategies (GLOB) when reading narrative texts, both Local and Western stories and also the effectiveness of this strategy around 75.55 (SD = 6.8) in the control class and 81.11 (SD = 3.9) inside the experimental class. Drawing on the findings, this study implied that metacognitive strategy can be adopted in the teaching reading in secondary school context.